Root hydraulic conductivity and adjustments in stomatal conductance: hydraulic strategy in response to salt stress in a halotolerant species - Vitali, Victoria Andrea; Bellati, Jorge; Soto, Gabriela Cynthia; Ayub, Nicolás Daniel; Amodeo, Gabriela (Oxford University Press, 2021)
Recent advances at the molecular level are introducing a new scenario that needs to be integrated into the analysis of plant hydraulic properties. Although it is not yet clear to what extent this scenario alters the current proposal for the hydraulic circuit models, it introduces new insights when studying plants that are able to easily overcome water restrictions. In this context, our aim was to explore water adjustments in a halotolerant model (Beta vulgaris) by studying the coordination between the root in terms of root hydraulic conductivity (Lpr) and the shoot as reflected in the stomatal conductance (gs). The root water pathways were also analysed in terms of root suberization (apoplastic barrier) and aquaporin transcript levels (cell-to-cell pathway). Beta vulgaris showed the ability to rapidly lose (4 h) and gain (24 h) turgor when submitted to salt stress (200 mM). The reduction profile observed in Lpr and gs was consistent with a coupled process. The tuning of the root water flow involved small variations in the studied aquaporin's transcripts before anatomical modifications occurred. Exploring Lpr enhancement after halting the stress contributed to show not only a different profile in restoring Lpr but also the capacity to uncouple Lpr from gs. Beta vulgaris root plays a key role and can anticipate water loss before the aerial water status is affected.